Useful Disasters: The Complexity of Response to Stress in a Tropical Lake Ecosystem - Pratt, Marion (Anthropologica, 2022)
The introduction of the Nile perch in the 1960s enhanced the economic value of the local fishery and encouraged women to become involved in fish processing and marketing. Over time, however, the predatory perch has severely reduced stocks of popular indigenous fishes. Currently, competition created by high foreign demand for the perch is forcing small-scale traders out of business and depriving local consumers of fish protein. Case studies reveal that the increased competition also has elicited various forms of production relations among men and women processors and traders. The complexities associated with the socio-ecology of this ecosystem hinder attempts to develop effective management policies.